Sexualized drug use among men who have sex with men in Madrid and Barcelona: The gateway to new drug use? - Guerras, Juan-Miguel; Hoyos, Juan; Donat, Marta; de la Fuente, Luis; Palma Díaz, David; Ayerdi, Oskar; García-Pérez, Jorge N.; García de Olalla, Patricia; Belza, María-José (Frontiers in Public Health, 2022)
This original study compares the prevalences of drug use for any purpose and for sexualized drug use (SDU) among MSM. It also describes relevant characteristics of first SDU, analyzes to what extent SDU has been the first experience (the gateway) with different drugs by age and explores the correlates of SDU. Study participants included 2,919 HIV-negative MSM attending four HIV/STI diagnosis services in Madrid and Barcelona. They answered an online, self-administered questionnaire. Poisson regression models with robust variance were used. About 81.4% had ever used any drug, and 71.9% had done so in the last-12-months, while 56% had ever engaged in SDU, and 50% had done so in the last-12-months. Participants under 25 years old had the lowest prevalences of SDU, and the 25–39 age group the highest, except for Viagra, which was higher among those over age 40. The most frequently used drugs for first SDU were poppers (53.6%), cannabis (19.6%) and Viagra (12.2%). These drugs were also the most ever consumed for SDU. Among sexualized users, methamphetamine (78.3%) and Mephedrone (75.4%) were used always/most of the times for sex in the last-12-months. Around 72.2% of Mephedrone sexualized users and 69.6% of Methamphetamine vs 23.1% of ecstasy users' first consumption of these drugs involved use for sex. These drugs were provided to them free where they have sex for 66.8, 79.1, and 31.9%, respectively. On that occasion, 8.1% of Mephedrone, 6.8% of Methamphetamine and 18.4% of ecstasy users had sex only with steady partner; with 50.2, 56.2, and 26.2% respectively using a condom with any partner. SDU in the first use was associated with similar variables for recreational and chemsex drugs. The highest prevalence ratios were for having ever been penetrated by >20 men and having ever injected drugs. It can be concluded that the prevalence of SDU was more than half of the prevalence for any purpose. Thus SDU was the gateway to use for many drugs in an important proportion of users, who frequently consumed drugs that were free and had condomless anal sex with occasional and multiple partners. These circumstances were much more common for chemsex than for recreational drugs.